The spatial analysis for Greenhouses in province Baghdad - رباب جبار صبر (College of Education for Women, 2019)
Greenhouses are provide that produce of vegetable in non times seasons production by controlling the various environmental factors that appropriate atmosphere in temperature and humidity for the growth of plants in the plastic houses and owner plastic. The objective of this research is to study of the most important natural and human factors affecting the Greenhouses in the province of Baghdad and study geographic distribution for the Greenhouses in the province. Some properties on curriculum geographical descriptive analytical that used in describe and analysis of data and information that could be available from Directorate of agriculture in Baghdad to 2014. As it turns out that district of Mahmudiya acquired (45.3%) of the total homeowners agricultural in the province, as was the number of homeowners agricultural (859) owner and by (2931) plastic house while formed area under the plastic houses (609) acres , ie (32%) of the total area allocated for plastic houses in province of Baghdad. The results of the study the district of Mahmudiya acquired (87.8%) of the total homeowners of plastic tunnels, as was the number of tunnel owners agricultural (5791) owner and by (2258360) plastic tunnel, while formed area under the agricultural tunnels (70295) acres , ie (98.8%) of the total area allocated for plastic tunnels in province of Baghdad.